(3jGfY GdGSJaGOIs - (3eUWai (B((3Ch eMeO eUWai(B) (3Hf eMeO aGVd Hf eMeO Cejf GdTfbjWj Gdbdbej, CHh GdCfhGQ, GdedbH HeGA GdYjfjf, J (B1328 (3g` s
(3ChdgG (B:s
(3bGd YHjO Gddg eGA GdYjfjf jQLh UdGM GdbdH hGdOGQjf hHYO aPG fXe jSJajO Hg GdPi CNPg ef GdYHjO CNPJ ef cJGH SHd GdEQTGO dYdg jQTO ef efg ESJaG QJHJg JQJjHg Ydi GdMQha s
(3BNQgG (B:s
(3dPGc aGSJca HeG bO PcQG hGdMeO ddg BNQ GdOYhi EP gh CaVd GdPi bO jghi CfJgJ s
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJHJ GdYfGhjjf hGdVHW HGdMeQIs
(3efXheI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B243 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B281s
Keywords: (3GdJUha hGdBOGH GdTQYjIs